Reconvexo : reurbanização do bairro Chácara Bela Vista em Passo Fundo - Santos, Any Caroliny Martin dos (2022)
Reconvexo represents the invisible struggle that more than 5 million families have against social inequality in Brazil. According to the IBGE, in 2019 there were approximately 13,000 substandard housing clusters in Brazil. In the municipality of Passo Fundo, in the same year, approximately 50 areas of irregular occupation within the urban territory were cataloged. From this scenario, this work investigated solutions for the housing deficit in the mentioned city through the land regularization of occupied areas, seeking to integrate, together with the owners of the lots, the qualification of the neighborhood, the promotion of sustainability allied to the regeneration of the river and the income generation for residents. In this way, this project related different levels of intervention, going through the individual lots of each inhabitant and their dimensions, to the proposition of a new municipal public library for common use by the entire community.